THE IMPACT OF DIGITAL MARKETING ON CONSUMER PURCHASE DECISIONS (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2026)
Digital marketing has become an important factor influencing consumer behavior and purchase decisions in today’s business environment. The development of digital technologies and online platforms has changed the way companies communicate with customers and promote their products and services. This study examines the impact of digital marketing on consumer purchase decisions by focusing on tools such as social media marketing, online advertising, content marketing, and personalized communication. The analysis shows that effective digital marketing strategies increase consumer awareness, improve customer engagement, and positively affect purchasing intentions. In particular, personalized content and active online interaction help build trust and encourage consumers to choose specific products or brands. In addition, digital marketing provides businesses with opportunities to better understand consumer preferences and respond more effectively to market changes. Through continuous interaction and data-driven communication, companies can create more personalized experiences that increase customer satisfaction and strengthen long-term loyalty. As a result, digital marketing has become not only a promotional tool but also an important element of sustainable business growth. The study concludes that digital marketing plays a significant role in modern business and contributes to stronger customer relationships and competitive advantage.